THE EFFECT OF ARTIFICIAL INTELLIGENCE ON CRITICAL THINKING IN STUDENT LEARNING - Dinda Aulia; Misrah Misrah (LP2M IAI Al-Khairat Pamekasan, 2026)
The increasing use of artificial intelligence (AI) in higher education has the potential to influence students’ critical thinking skills. This study aimed to examine the effect of artificial intelligence on the critical thinking skills of students in the Islamic Guidance and Counseling Study Program at Universitas Islam Negeri Sumatera Utara and to compare the tendency of this effect between the 2022 and 2025 cohorts. This study employed a quantitative explanatory design. The population consisted of 114 active students from the 2022 and 2025 cohorts, all of whom were included as respondents using saturated sampling. Data were collected through a four-point Likert-scale questionnaire and analyzed using simple linear regression. The research instrument met the validity criteria and demonstrated very high reliability, with a Cronbach’s alpha value of 0.925. The findings revealed that artificial intelligence had a positive and significant effect on students’ critical thinking skills, with a regression coefficient of 0.526, a t-value of 7.814, and a significance value of 0.000. The coefficient of determination of 0.347 indicated that artificial intelligence explained 34.7% of the variance in students’ critical thinking skills. Cohort-based analysis showed that the effect of AI was stronger among the 2022 cohort (R^2 = 0.243) than the 2025 cohort (R^2 = 0.104). These findings indicate that AI can support critical thinking when it is used actively to explore information, evaluate responses, compare perspectives, and construct arguments. Therefore, AI integration in Islamic Guidance and Counseling learning should be implemented critically, reflectively, ethically, and in ways that preserve students’ independent learning.